PENGARUH KESADARAN MEREK, ELECTRONIC WORD OF MOUTH DAN SALURAN PEMASARAN DIGITAL TERHADAP KEPUTUSAN PEMBELIAN BUAH-BUAHAN MELALUI E-GROCERY - Amalia, Vinka Riski; Adiarni, Nunuk; Aminudin, Iwan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Had been carried out regarding influence of brand awareness, electronic word of mouth and digital marketing funnel on buying decision of fruits through e-grocery. Respondents were determined using the sample method. The sample size was 100 people taken from an unknown population of fruit buyers through e-grocery. Descriptive tabulation and SEM analysis of the PLS approach are used to determine the effect of brand awareness, electronic Word of Mouth (eWOM) and digital marketing funnel on consumer behavior, on purchasing decisions and on fruit purchase decisions based on e-grocery consumer behavior variables. The results showed that (1) electronic word of mouth and digital marketing channels have a real and significant effect on consumer behavior. Brand awareness has significant effect on consumer behavior, (2) electronic word of mouth, digital marketing channels and consumer behavior have significant effect on purchasing decisions and (3) electronic word of mouth and digital marketing channels have significant effect on purchasing decisions based on consumer behavior variables. Brand awareness has no real and significant effect on purchasing decisions based on consumer behavior variables.